Prognostic factors in patients with primary cutaneous anaplastic large cell lymphoma: a multicentric, retrospective analysis of the Spanish Group of Cutaneous Lymphoma. (19th November 2019) - Fernández‐de‐Misa, R.; Hernández‐Machín, B.; Combalía, A.; García Muret, M.P.; Servitje, O.; Muniesa, C.; Gallardo, F.; Pujol, R.M.; Martí, R.M.; Ortiz‐Brugués, A.; Maroñas‐Jiménez, L.; Ortiz‐Romero, P.L.; et al.
Abstract: Background: Reliable prognostic factors for patients with primary cutaneous anaplastic large cell lymphoma (PCALCL) are lacking. Objective: To identify prognostic factors for specific survival in patients with PCALCL. Methods: Using the convenience sampling method, patients with PCALCL diagnosed from May 1986 to August 2017 in 16 University Departments were retrospectively reviewed. Results: One hundred eight patients were included (57 males). Median age at diagnosis was 58 years. All of them showed T1‐3N0M0 stages. Seventy per cent of the cases presented with a solitary lesion, mostly at the limbs. Complete response rate after first‐line treatment was 87%, and no advantage was observed for any of them (surgery, radiotherapy, chemotherapy or other approaches). Nodal and visceral progression rate was 11% and 2%, respectively. 5‐year specific survival (SSV) reached 93%; 97% for T1 patients and 84% for T2/T3 patients ( P  = 0.031). Five‐year SSV for patients developing early cutaneous relapse was 64%; for those with late or no relapse, 96% ( P  = 0.001). Estimated median SSV for patients showing nodal progression was 103 months (95% CI: 51–155 months); for patients without nodal progression, estimated SSV did not reach the median ( P  < 0.001). Nodal progression was an independent predictive parameter for shorter survival ( P  = 0.011). Conclusion: Multiple cutaneous lesions at presentation, early skin relapse and nodal progression portrait worse prognosis in patients with PCALCL.